The effect of microscopic cracks on chloride diffusivity of recycled aggregate concrete. (10th May 2018) - Wu, Yu-Ching; Xiao, Jianzhuang
Highlights: A novel stochastic numerical method to investigate the effect of cracks on diffusivity of RAC. Two-dimensional fictitious multi-phase RAC models are randomly generated. Effective homogenized ion diffusion coefficients of RAC models are computed using RVE approach. Microscopic defect number, direction, and length might have significant influence. Abstract: This study proposes a novel stochastic numerical method to investigate the effect of microscopic cracks on chloride diffusivity of recycled aggregate concrete. First of all, two-dimensional fictitious multi-phase recycled aggregate concrete (RAC) models are randomly generated. The fictitious RAC models consist of microscopic cracks in addition to natural aggregate, old interfacial transition zones (ITZs), old mortar, new ITZs, and new mortar. Next, effective homogenized ion diffusion coefficients of RAC models are computed using representative volume element (RVE) approach, after the size of RVE is determined by convergence analysis. Then a series of Monte Carlo simulations are made to explore the link between randomly distribution of microscopic cracks and the effective homogenized ion diffusivity. Finally, the numerical experimental results indicate that microscopic defect number, direction, and length might have significant influence on the effective homogenized ion diffusion parameter of RAC. In addition, this study investigates material property uncertainties of ITZs and mortar on the global chloride diffusivity of RAC. Final results demonstrate that effects from material property uncertainties of ITZs and mortar might be negligible.